1988
DOI: 10.1111/j.1365-2621.1988.tb07776.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Concentration of Red Wine by Reverse Osmosis

Abstract: A reverse osmosis process using membranes with a specific ethanol exclusion rate of 85% was effective in concerning red wines. In order to increase 1% wine ethanol content, a loss of only 2% total pure ethanol was observed. The permeate flow rate was about 2 L/hr/mz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…4). These values confirmed those reported by Bui et al (1988) who increased the concentration of alcohol in wine from 11.5 to 12.5% ethanol, noting an 85% rejection of ethanol.…”
Section: Initial Analysis Of Pressure and Temperaturesupporting
confidence: 94%
See 1 more Smart Citation
“…4). These values confirmed those reported by Bui et al (1988) who increased the concentration of alcohol in wine from 11.5 to 12.5% ethanol, noting an 85% rejection of ethanol.…”
Section: Initial Analysis Of Pressure and Temperaturesupporting
confidence: 94%
“…Sheu and Wiley (1983) concentrated 10"Brix apple juice (at 25°C) to 20-25"Brix with high retention of volatiles and showed that lower operating temperatures gave better recovery of volatiles. Experiments with wine showed no loss of color with membrane concentration at 14.3% ethanol (Bui et al, 1988). Matsuura et al (1974) evaluated concentration of apple juice and showed that, as concentration increased, the osmotic pressure of the juice increased and the flux, or production of permeate, decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Most other constituents were found at trace levels in the permeate except methanol, which can cross the membrane freely. 187,188 In this manner, it is possible to take a low-acid, light-colored, and light-bodied red wine and, by RO concentration, produce a full-bodied, dark-colored, high-acid product.…”
Section: G Ro Applications In Enologymentioning
confidence: 99%
“…the preparation of milk (Glover 1971) and fruit juice concentrates (Paulsen et al 1985, Kane et al 1995. Within the wine industry, reverse osmosis has been used to manipulate wine alcohol content, volatile acidity and acidification through concentration of grape must (Duitschaever et al 1991) and wine (Bui et al 1988, Massot et al 2008. Reverse osmosis has also been coupled with solid phase adsorption to remove 4-ethylguaiacol and 4-ethylphenol from Brettanomyces-affected wine (Ugarte et al 2005).…”
Section: Introductionmentioning
confidence: 99%